International guidelines regarding the role of IVIG in the management of Rh‐ and ABO‐mediated haemolytic disease of the newborn. (12th April 2022) - Lieberman, Lani; Lopriore, Enrico; Baker, Jillian M.; Bercovitz, Rachel S.; Christensen, Robert D.; Crighton, Gemma; Delaney, Meghan; Goel, Ruchika; Hendrickson, Jeanne E.; Keir, Amy; Landry, Denise; La Rocca, Ursula; et al.
Abstract: Haemolytic disease of the newborn (HDN) can be associated with significant morbidity. Prompt treatment with intensive phototherapy (PT) and exchange transfusions (ETs) can dramatically improve outcomes. ET is invasive and associated with risks. Intravenous immunoglobulin (IVIG) may be an alternative therapy to prevent use of ET. An international panel of experts was convened to develop evidence‐based recommendations regarding the effectiveness and safety of IVIG to reduce the need for ETs, improve neurocognitive outcomes, reduce bilirubin level, reduce the frequency of red blood cell (RBC) transfusions and severity of anaemia, and/or reduce duration of hospitalization for neonates with Rh or ABO‐mediated HDN. We used a systematic approach to search and review the literature and then develop recommendations from published data. These recommendations conclude that IVIG should not be routinely used to treat Rh or ABO antibody‐mediated HDN. In situations where hyperbilirubinaemia is severe (and ET is imminent), or when ET is not readily available, the role of IVIG is unclear. High‐quality studies are urgently needed to assess the optimal use of IVIG in patients with HDN.